2016
DOI: 10.1152/advan.00193.2015
|View full text |Cite
|
Sign up to set email alerts
|

First-year medical students' naïve beliefs about respiratory physiology

Abstract: The present study explored the nature and frequency of physiology naïve beliefs by investigating novices' understanding of the respiratory system. Previous studies have shown considerable misconceptions related to physiology but focused mostly on specific physiological processes of normal respiration. Little is known about novices' broader understanding of breathing in a clinical context. Our study hypothesized that naïve beliefs could hamper participants' ability to understand the interrelatedness of respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…A possible explanation could be that some students are not able to apply their knowledge to organs that cannot be seen or to structures at the micro level. This same misconception was reported by Badenhorst et al (2016) in a study concerning the naïve beliefs of first-year medical students regarding respiratory physiology.…”
Section: Discussionsupporting
confidence: 69%
“…A possible explanation could be that some students are not able to apply their knowledge to organs that cannot be seen or to structures at the micro level. This same misconception was reported by Badenhorst et al (2016) in a study concerning the naïve beliefs of first-year medical students regarding respiratory physiology.…”
Section: Discussionsupporting
confidence: 69%
“…Whereas Phys-MAPS is not solely based in human physiology, it is highly conceptually relevant to the field, and first-year medical students often have naive conceptions of the most difficult concepts on Phys-MAPS, such as homeostasis (e.g., Ref. 7).…”
Section: Recommended Usementioning
confidence: 99%
“…There is empirical evidence of the existence of misconceptions in medical education. Biomedical misconceptions have been investigated mainly in physiology, particularly in the respiratory (12)(13)(14)(15)(16) and cardiovascular systems (11,13,(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular system poses particular conceptual difficulties, specifically with integrating anatomical and physiological knowledge (23), assimilating the role of biochemical and physiological processes (18,19), and drawing on a coherent understanding of physics and chemistry (21). Studies about respiratory misconceptions found that medical students draw on teleological explanations to describe breathing (12,25), they struggle to understand the mechanics of breathing (9,12), and they have misconceptions related to the underlying physiological processes (15,26). Research on misconceptions in the field of cell biology and histology is limited and mainly focuses on conceptual difficulties students experience with regards to cell processes, genes, and chromosomes (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%